Thomas Hardy entre fiction et poésie - Jean-Charles Perquin (Cahiers Victoriens et Edouardiens)
Thomas Hardy was born in 1840 and is still known today for the decades he devoted to the art of fiction and the numerous novels and short stories he wrote. But the novelist is far less known for the poetry he persistently composed. In 1898, he suddenly decided to stop writing fiction and devote himself to poetry only. This paper intends to explore not only his choice but the way Hardy always had of resorting to both fiction and poetry, as if the limit were but artificial and alien to his art.